Politik Teritorial dan Perampasan Tanah-Hutan di Desa Lingkar Tambang Bijih Besi, Kecamatan Lede, Kabupaten Taliabu, Provinsi Maluku Utara - Rahmat Hidayat (Universitas Muslim Maros, 2020)
The country's territorial politics that divide natural resources into specific arrangements, such as the determination of forest areas, has facilitated the presence of PT. Adidaya Tangguh in the Taliabu forest. Its presence has usurped traditional community ownership rights over its natural resources (land and forest). This condition does not make the community to remain silent. Various methods have been taken into account, from contesting the tribal ulayat land discourse, to the resistance movement through demonstrations that hold companies accountable for the losses they experience. This article aims to explore how the traditional landscape form of the Mange tribe and how mining expansion which is facilitated by all state instruments is resisted by the community. This research was carried out in two villages around the mine in Lede Subdistrict, Tolong and Todoli Villages, Taliabu District, North Maluku between June and August 2019. Data was collected using in-depth interview and observation. The informants in this study consisted of three elements: first, Mining Officers of North Maluku Province, second, PT. Adidaya Tangguh employees, and third, the village community in around mining company. The research findings indicate the existence of local concepts related to the meaning of space by the Mange people in the villages of Todoli and Tolong who had lived in the form of a unitary autonomous local institutions, small communities called Soa long before the existence of an independent Indonesian state as a nation. The traditional territorial concept of the Mange people regarding forest land is no longer considered as a primary forest (kalia) which is sacred to the Mange tribal community, but as a unity of hamlets and memorial heritages of the ancestors of the Mange tribe. After carrying out the incorporation of the modern government system, the Mange tribe was gradually weakened. The expansion of mining capital to their regions facilitated by local governments has taken and destroyed their forests. This appropriation has caused turmoil in the community in the form of open resistance, by sounding their demands to PT. Adidaya Tangguh through adat resistance movements and farmers in the villages of Todoli and Tolong. This resistance got repression, violence and terror from the state.